Low Level Laser Therapy With an 810-nm Diode Laser Affects the Proliferation and Differentiation of Premature Osteoblasts and Human Gingival Fibroblasts In Vitro: LLLT 810nm effect on osteoblasts, gingival fibroblasts and co-cultures - Bourouni, Ioanna; Kyriakidou, Kyriaki; Fourmousis, Ioannis; Vrotsos, Ioannis; Karoussis, Ioannis (Journal of Lasers in Medical Sciences, 2021)
Introduction: Photomodulation is a promising strategy for optimizing tissue healing, but its photomodulatory effects on the synergistic cellular metabolism of gingival and bony tissues remain largely unknown. The aim of the present study was to evaluate the photomodulatory effects of a diode laser (810 nm) on osteoblasts, HGFs, and their co-cultures in vitro. Methods: Primary cultures of HGFs, cultures of immature osteoblastic cells (MG63), and their cocultures were irradiated with a diode laser (810 nm), 15 J/cm2. Cell cultures were examined for cellular proliferation (MTT assay), viability (FDA/PI staining) after 24, 48, and 72 hours, and cell differentiation (qPCR of collagen type 1a – COL1a and alkaline phosphatase expressions - ALP) after 7 days. Results: Photomodulation with an 810-nm diode laser increased cell proliferation at all time points. COL1a gene expression increased both in HGF and co-cultures. ALP expression was up-regulated in osteoblastic cultures, but co-cultures with fibroblasts negated this response. Conclusion: The 810-nm diode laser positively affected cell proliferation and viability in all experimental groups. The statistically significant increased COL1a gene expression at 7 days after irradiation both in the irradiated HGF and co-cultures suggests that low-level laser therapy (LLLT) stimulated extracellular matrix (ECM) formation signaling in both cell types. DOI: 10.34172/jlms.2021.33